Composition of the ruling elite, incentives for productive usage of rents, and prospects for Russia's limited access order. Issue 5 (3rd September 2021) - Yakovlev, Andrei
ABSTRACT: Vladimir Putin's personal popularity creates the base for sociopolitical stability of regime. However, in the long term, the aspirations of Russia's elite for national sovereignty will come to naught without anew economic development model. Applying the "limited access orders" framework of North, Wallis, and Weingast, this essay analyzes the interactions among three key groups in the ruling elite# the top federal bureaucracy, politically connected big business (oligarchs), and heads of security forces (siloviki). It considers the evolution of rent sources in Russia during the last 25 years and the incentives of elite groups. Itargues that under dominance of siloviki after 2012, the ruling coalition could not negotiate anew agreement on rent distribution, nor could it broaden access to economic opportunities and political activity for new social groups. Russia's ruling elite missed the opportunity to avoid adeep shock that will likely destroy the existing "limited access order".